EFIKASI DIRI DALAM MEMEDIASI PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA - Ikhlas Ul Aqmal; Hendra Pratama Danial; Aurelia Revalina Anwar; Putri Jesica Aulia Haq (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2025)
The purpose of this study was to determine the impact of self-efficacy in mediating the influence of budget participation on performance in the Gorontalo Provincial Government. Data were analyzed using SEM-PLS assisted by WarpPLS software. SEM-PLS allows testing the direct effect of budget participation on performance and the indirect effect between budget participation and performance through self-efficacy. The findings of this study indicate that self-efficacy partially mediates the effect of budget participation on performance. A limitation of this study is the use of questionnaires to obtain primary data, which relies on respondents' perceptions and, therefore, may contain subjective factors. A second limitation is the generalizability of the sample.